2020
DOI: 10.3126/jmmihs.v6i1.30532
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patients’ Knowledge, Perception and Safety Regarding MRI Scan

Abstract: Correction: The page numbers on this article were changed from 4-20 to 3-19 on 31/08/2020. Introduction: We presume that the knowledge of patients about Magnetic Resonance imaging (MRI) scan is of utmost importance for smooth workflow, patient comfort, patients’ safety and to mitigate patients’ compliance and save valuable scan time. Therefore, the purpose ofthis study was to determine the awareness of patients undergoing MRI scan regarding Knowledge, Perception and Safety. Methods: This descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…5 The results are similar to the study conducted by Shrestha et al 9 that were 7.7% patients thought that MRI is safe for pregnant women and while 88.1% patients thought didn't safe. 4 Results also same to the study conducted by S. Asante et al that 57% patients responded its safe while 32.5% stated it was whilst and rest 10.5% didn't have idea regarding this. 7…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…5 The results are similar to the study conducted by Shrestha et al 9 that were 7.7% patients thought that MRI is safe for pregnant women and while 88.1% patients thought didn't safe. 4 Results also same to the study conducted by S. Asante et al that 57% patients responded its safe while 32.5% stated it was whilst and rest 10.5% didn't have idea regarding this. 7…”
Section: Discussionsupporting
confidence: 83%
“…The lack of knowledge regarding MRI safety can lead to anxiety, stress, and unnecessary delays in the MRI process. 4 The perception of MRI safety among patients is a growing concern in the healthcare industry, and numerous studies have been conducted to evaluate patients' understanding of MRI safety. These studies have highlighted the need for more effective communication strategies to enhance patients' knowledge and perception of MRI safety.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, Alghamdi and Shrestha reported similar findings. 12 , 15 Furthermore, it was reported that MRI technologists must keep patients safe and be capable of assessing MRI safety, patients’ conditions, and compatibility of medical devices. 15 This increases the need for patients to understand MRI examinations, which in most cases require preparations to improve image quality.…”
Section: Discussionmentioning
confidence: 99%
“…The problem at hand is multifaceted and requires exploration to comprehensively address the intricacies of the nursing profession in Nepal. Firstly, the demanding nature of nursing in the Nepalese healthcare system is characterized by long working hours, high patient-to-nurse ratios, and challenging working conditions (Shrestha, 2017). These factors can potentially impede the overall QWL of nurses, affecting their job satisfaction and, subsequently, their ability to achieve a satisfactory work-life balance.…”
Section: Introductionmentioning
confidence: 99%